2007
DOI: 10.1111/j.1439-0442.2007.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Microsatellite Markers for Genetic Analysis of Collagen Genes in Suspected Collagenopathies in Dogs

Abstract: Defects in collagen proteins cause a variety of disorders in humans. It can be expected that collagen gene mutations are involved in collagenopathies in dogs. The collagen genes COL3A1, COL5A1, COL5A2, COL6A1, COL6A3, COL9A1, COL9A2, COL9A3, COL10A1 and COL11A1 were identified on the canine genome based on the homology with the human genes. Simple sequence repeats (microsatellites) were found in the chromosomal regions of these genes and investigated for polymorphism in Labrador Retrievers, Bernese Mountain do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The different incidence of CCL rupture in certain breeds could indicate that the condition may have a genetic basis. Heritability of CCL rupture has been studied in Newfoundlands, Boxers and Labrador Retrievers (Wilke et al 2006, Temwichitr et al 2007, Clements et al 2010, Comerford et al 2011. However, the genetics of CCL disease in small breed dogs have not yet been investigated to our knowledge.…”
Section: Breedmentioning
confidence: 99%
“…The different incidence of CCL rupture in certain breeds could indicate that the condition may have a genetic basis. Heritability of CCL rupture has been studied in Newfoundlands, Boxers and Labrador Retrievers (Wilke et al 2006, Temwichitr et al 2007, Clements et al 2010, Comerford et al 2011. However, the genetics of CCL disease in small breed dogs have not yet been investigated to our knowledge.…”
Section: Breedmentioning
confidence: 99%
“…The exclusion analysis method was used to identify the mutation that causes oculocutaneous albinism in Doberman Pinscher dogs . Several other research groups have also used a similar approach to exclude candidate genes as being causative for other phenotypes . It is important to note that inability to exclude a gene is not direct evidence, it is causative of the phenotype (there is a probability that a MS allele could be fixed within a breed), but it does suggest that a closer examination of that gene is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…No significant association was found with COL9A3 and ACL rupture in the population of 90 Newfoundland dogs. Another candidate gene study found no association with COL9A3 and ACL rupture in 12 Boxers [92]. Despite the Newfoundland and Boxer representing high-risk ACL rupture breeds, the candidate gene approach is most successful at identifying large effect mutations associated with monogenic traits and is limited at complex disease small-effect variant discovery [93].…”
Section: Plos Onementioning
confidence: 99%